PENGARUH PERSEPSI INVESTASI TERHADAP MINAT INVESTASI DI PASAR MODAL PADA GALERI INVESTASI BEI UNIVERSITAS BATURAJA - Indra Yadi; Yopi Yunsepa (STIE DWI SAKTI BATURAJA, 2022)
This study aims to how is the effect of investment perception on interest in investing in the Capital Market at the IDX Investment Gallery, Baturaja University. The method in this research is descriptive method. The sample in this study were 53 investors in the BEI investment gallery at Baturaja University. Based on the simple linear regression equation, it is Y=13.071 + 0.367X, and the correlation value is 0.378. This value indicates that the relationship between the independent variable, namely investment perception and the dependent variable, is not very strong. While the r-square number (Coefficient of Determination) is 0.143, this value indicates that the contribution of the independent variable, namely investment perception with the dependent variable, namely investment interest, simultaneously is 14.3% while the remaining 85.7% is not examined in this study. Based on the data obtained, the tcount of the X variable is 2,912 where the tcount is more than the ttable value (2,912 < 2,007), then Ho is rejected and Ha is accepted, meaning that there is a partial influence between the investment perception variable (X) and the investment interest variable (Y). at the IDX Investment Gallery, Baturaja University.